A Comparison of the Thompson Encephalopathy Score and Amplitude-Integrated Electroencephalography in Infants with Perinatal Asphyxia and Therapeutic Hypothermia - Weeke, Lauren C. (Neonatology, 2017)
BACKGROUND: In previous studies clinical signs or amplitude-integrated electroencephalography (aEEG)-based signs of encephalopathy were used to select infants with perinatal asphyxia for treatment with hypothermia. AIM: The objective of this study was to compare Thompson encephalopathy scores and aEEG, and relate both to outcome. SUBJECTS AND METHODS: Thompson scores, aEEG, and outcome were compared in 122 infants with perinatal asphyxia and therapeutic hypothermia. Of these 122 infants, 41 died and 7 had an adverse neurodevelopmental outcome. A receiver operating characteristics (ROC) analysis was also performed. RESULTS: Thompson scores were higher in infants with more abnormal aEEG background patterns (ANOVA, p < 0.001). The ROC analysis demonstrated that a Thompson score of 11 or higher or an aEEG background pattern of continuous low voltage or worse was associated with an adverse outcome (AUC 0.84 for both). CONCLUSIONS: High Thompson scores and a suppressed aEEG background pattern are associated with an adverse outcome after perinatal asphyxia and therapeutic hypothermia. Further studies are needed to identify the best technique with which to select patients for therapeutic hypothermia